PENGARUH ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN SUSU PASTEURISASI DI RUMAH SUSU KUD ARGOPURO KECAMATAN KRUCIL KABUPATEN PROBOLINGGO - Nina Yunita; Aminah Happy Moninthofa Ariyani; Ihsannudin Ihsannudin (Universitas Sebelas Maret, 2024)
Indonesia has the opportunity to increase cow's milk production, but the level of milk consumption among Indonesian people is much lower than in neighboring countries. The imbalance of large production quantities with the low market demand can cause price declines. In order not to experience losses, producers must be consumer-oriented. The aims of this study were to analyze the characteristics of consumers of pasteurized milk at the KUD Argopuro Dairy House and to analyze the effect of the attributes of pasteurized milk on consumers. The research method used descriptive analysis to answer the first purpose and conjoint analysis for the second purpose. The number of samples in this study was 96 respondents. Characteristics consumers of pasteurized milk at the KUD Argopuro Dairy House were mostly women, aged 21 until 25 years, with a high school equivalent final education level, dominated by students, with a monthly income of less than Rp500.000. Consumers prefer chocolate-flavored pasteurized milk in 1.000 ml plastic bottles for Rp6.000. Consumers consider is the taste of the milk, the size of the package, the type of packaging, and the price. Suggestions that can be given are to increase the production of chocolate flavored pasteurized milk so that the product sells faster, develop 1.000 ml packaging in plastic bottles so that it is not inferior to competing products, and set a more affordable price for consumers which are students.